Clinging on to alpine life: Investigating factors driving the uphill range contraction and population decline of a mountain breeding bird - Ewing, Steven R.; Baxter, Alistair; Wilson, Jeremy D.; Hayhow, Daniel B.; Gordon, James; Thompson, Des B. A.; Whitfield, D. Philip; van der Wal, René (Global change biology, 2020)
Climate change and anthropogenic nitrogen deposition are widely regarded as important drivers of environmental change in alpine habitats. However, due to the difficulties working in high‐elevation mountain systems, the impacts of these drivers on alpine breeding species have rarely been investigated. The Eurasian dotterel (Charadrius morinellus) is a migratory wader, which has been the subject of uniquely long‐term and spatially widespread monitoring effort in Scotland, where it breeds in alpine areas in dwindling numbers. Here we analyse data sets spanning three decades, to investigate whether key potential drivers of environmental change in Scottish mountains (snow lie, elevated summer temperatures and nitrogen deposition) have contributed to the population decline of dotterel. We also consider the role of rainfall on the species' wintering grounds in North Africa. We found that dotterel declines—in both density and site occupancy of breeding males—primarily occurred on low and intermediate elevation sites. High‐elevation sites mostly continued to be occupied, but males occurred at lower densities in years following snow‐rich winters, suggesting that high‐elevation snow cover displaced dotterel to lower sites. Wintering ground rainfall was positively associated with densities of breeding males two springs later. Dotterel densities were reduced at low and intermediate sites where nitrogen deposition was greatest, but not at high‐elevation sites. While climatic factors explained variation in breeding density between years, they did not seem to explain the species' uphill retreat and decline. We cannot rule out the possibility that dotterel have increasingly settled on higher sites previously unavailable due to extensive snow cover, while changes associated with nitrogen deposition may also have rendered lower lying sites less suitable for breeding. Causes of population and range changes in mountain‐breeding species are thus liable to be complex, involving multiple anthropogenic drivers of environmental change acting widely across annual and migratory life cycles. Impacts of climate change and anthropogenic nitrogen deposition on alpine breeding species have rarely been investigated due to the challenges of working in such environments. Using a uniquely long‐term and spatially‐widespread monitoring dataset for Eurasian dotterel in Scotland, we demonstrate that this species declined and disappeared disproportionately from low and intermediate elevation alpine sites, providing a rare example of a high‐elevation specialist retreating at the trailing‐edge of its elevational range. Dotterel breeding densities were influenced by snow‐lie and nitrogen deposition on alpine breeding sites, and rainfall on their wintering grounds, but there is limited evidence these underpin the actual uphill range retraction range.